Motives and Risk Factors of Problematic Engagement in Online Sexual Activities. Issue 3 (2nd October 2019) - Bolshinsky, Valeriya; Gelkopf, Marc
Abstract: Motives and risk factors associated with problematic engagement in online sexual activities (OSAs) have been poorly explored. The current study aimed to examine motives, gender, history of childhood maltreatment, and adult attachment types as possible risk factors associated with problematic OSAs. Two hundred eighty-four responders took part in an online survey. A significant part of the sample admitted experiencing distress and having adverse consequences on their work or school performance because of their OSAs. Having a history of greater childhood maltreatment was associated with a higher tendency to adopt mood regulation, anonymous fantasizing, socializing/seeking intimacy, and sexual pleasure motives for OSAs. Participants with more problematic OSAs tended to adopt more frequently mood regulation, anonymous fantasizing, socializing/seeking intimacy, and sexual pleasure motives for their engagement compared with participants with less problematic OSAs. Multiple regression analyses indicated that problematic OSAs were mostly predicted by sexual pleasure motives among female participants and by mood regulation motives among male participants. Avoidant adult attachment type explained problematic OSAs among female users only. The findings of this study lend support for using motives checklist as a part of a problematic OSAs assessment.